Experimental and theoretical studies of levitated quantum fluids - Halley, J. W.; Schmidt, J.; Giese, C. F. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1998)
We describe the opportunities for improved scientific understanding and technical manipulation of cryogenic fluids, particularly molecular hydrogen, by the use of carefully designed magnetic field configurations produced with assemblies of permanent magnets. We discuss the levitation of hydrogen in order to perfect technical means for handling this and other cryogenic fluids. The development of the techniques to be explored here provide extraordinary opportunities for improved methods for handling rocket fuels and cryogenic fluids in low gravity environments.